Knowledge sharing intention at Malaysian higher learning institutions: the academics’ viewpoint - Fauri @ Fauzi, Muhammad Ashraf; Nya-Ling, Christine Tan; Thurasamy, Ramayah (Hong Kong Bao Long Accounting And Secretarial Limited, 2018)
Knowledge sharing (KS) is a culture that has been fostered and supported in higher learning institutions (HLIs) in Malaysian. This research applies Theory of Planned Behavior (TPB) and Social Capital Theory (SCT) to determine the factors associated with Malaysian academic's KS intention in HLIs. The results indicate that social networking is an important factor of academics’ attitude to KS, while commitment and trust do not influence their attitude to KS. Using social media is found to be a significant factor of perceived behavioral control towards KS. Further, academics’ attitude to KS and perceived behavioral control towards KS are found to be significant determinants of their KS intention, while management support for subjective norm of KS is not significant for KS intention.